This will be fun : a novel - Asher, E. B. (Avon, an imprint of HarperCollinsPublishers, 2024)
A group of friends, who once saved their magical land together but haven't spoken in 10 years, reunite to attend a royal wedding and end up on a new quest to defend the realm.